Aperture area measurement using two different traceability routes. (22nd October 2015) - Littler, I C M; Atkinson, E G; Manson, P J; Ballico, M; Kosubek, E; Taubert, D; Hollandt, J
Abstract: Given the advances in cryogenic radiometry, area measurement is now one of the limiting factors in the realisation of radiometric and photometric units as well as radiometric temperature scales. An inter-comparison of aperture area measurements using complementary methods at two different national metrology institutes has shown excellent agreement in the values measured, with the measurements agreeing well within the 95% confidence intervals. Importantly, the statistical scatter of the values is consistent with the magnitude of the confidence intervals, implying that the estimates of uncertainty are not overly conservative. This provides increased confidence to both institutes that systematic errors have not been overlooked and that the uncertainty contributions have been realistically assessed.